A LUDIC OPERA: “POST-FICTION” BY DAN DEDIU - HÎRLAV MAISTOROVICI, Sanda (Studia Universitatis Babes-Bolyai Musica, 2015)
The article A Ludic Opera: Post-Fiction by Dan Dediu comprises a short presentation of the composer’s older opus, which was performed for the first time at The International Week of New Music in 1996. Starting from musicologist Irinel Anghel’s remark that the opus has “a typically post-modern, opera-within-an-opera character”, the article advances an analytical framework that leads to the idea that the structure of the libretto and the musical scaffolding manifest filiations from and connections with Pirandelli’s outlook on theatre. The analytical inquiry highlights five arguments that support this hypothesis: the characters are entities that pertain to other operas; placed in another time and space, they behave as indignant characters; in their new stances, these characters undergo changes both at the level of their own personality and at the level of their image, reflected as if in a mirror, in the other characters’ consciousness; between the composer and his characters there is an interrelationship, the composer himself being part of the imaginative play of the performance.